Tackling overutilization of hospital tests and treatments: Lessons learned from a grassroots approach. Issue 5 (September 2018) - Hicks, Lisa K.; O'Brien, Patrick; Sholzberg, Michelle; Veloce, Nicole; Trafford, Anne; Sinclair, Doug
Recent data suggest unnecessary medical testing and treatment is relatively common in Canada. A number of harms to patients can arise as a result of unnecessary tests and treatments. In addition to patient harm, unnecessary tests and treatments add to the cost of medical care. Inspired by the Choosing Wisely campaign, St. Michael's Hospital in Toronto, Ontario, developed a hospital-wide program to address many different forms of overutilization at our hospital. The program prioritizes harm reduction over cost-containment and aims to create sustainable change through grassroots clinician engagement. This article will review important lessons learned from the St. Michael's experience.